Implementasi Strategi Marketing Berbasis Digital Dalam Meningkatkan Minat Calon Donatur Di Panti Asuhan Bilyatimi Surabaya - Erta Pramita; Diah Asmawardani, Elfira; Syahrengga Putra, Alvine; Ismail, Muhammad; Aulia Farah Tsania Amin, Nada; Ilham, Moh. (Journal of Islamic Management, 2025)
This research aims to analyze the implementation of digital-based marketing strategies in increasing the interest of potential donors at the Bilyatimi Orphanage in Surabaya. With the increasing development of technology and the use of social media, orphanages face challenges in attracting the attention and interest of potential donors, especially in the current digital era. This research uses a qualitative approach with descriptive methods to understand how digital marketing strategies seek to increase donor participation. Data was collected through interviews, observation and documentation. The research results show that digital marketing at Bilyatimi Surabaya Orphanage via instagram, tiktok, whatsapp, youtube and website can effectively show a positive impact in increasing potential donations received. By utilizing this digital platform, orphanages can attract the attention of donors. These findings provide an understanding of the use of digital marketing strategies in the context of social institutions, especially orphanages, which have their own characteristics.